2014
DOI: 10.1371/journal.pone.0105685
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Papaya Cell Wall-Related Genes during Fruit Ripening Indicates a Central Role of Polygalacturonases during Pulp Softening

Abstract: Papaya (Carica papaya L.) is a climacteric fleshy fruit that undergoes dramatic changes during ripening, most noticeably a severe pulp softening. However, little is known regarding the genetics of the cell wall metabolism in papayas. The present work describes the identification and characterization of genes related to pulp softening. We used gene expression profiling to analyze the correlations and co-expression networks of cell wall-related genes, and the results suggest that papaya pulp softening is accompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 45 publications
(77 reference statements)
7
51
0
Order By: Relevance
“…Transcriptome profiling of papaya has only been reported in the root (Porter et al 2008), flower (Urasaki et al 2012) and fruit (Fabi et al 2010(Fabi et al , 2014. Recently, a proteomic study in papaya callus showed that enolase, esterase and ADH to be potential biomarkers for somatic embryo in papaya (de Moura et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome profiling of papaya has only been reported in the root (Porter et al 2008), flower (Urasaki et al 2012) and fruit (Fabi et al 2010(Fabi et al , 2014. Recently, a proteomic study in papaya callus showed that enolase, esterase and ADH to be potential biomarkers for somatic embryo in papaya (de Moura et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the minor effect of PG silencing on tomato softening led to the view that PG-mediated pectin disassembly during ripening makes only a small contribution to fruit softening (Brummell & Harpster, 2001;Hadfield & Bennett, 1998). More recent studies on strawberry, apple and papaya have challenged this hypothesis, suggesting a key role for pectin modifications in fruit softening (Atkinson et al, 2012;Fabi et al, 2014;Jiménez-Bermúdez et al, 2002;Quesada et al, 2009;Youssef et al, 2009Youssef et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The R-1 and R-2 fruits had the lowest pulp firmness. The three PG genes evaluated were described in our previous studies 17,19 . The PG genes had their expression increased during fruit ripening, and PG1 was expressed in R-2 fruits almost 3,000 times more than in Un-1.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, papaya endogenous ethylene production is essential to induce www.nature.com/scientificreports www.nature.com/scientificreports/ the increase of PG activity and to solubilize cell wall polysaccharides 16,24 . PG is the main enzyme over-expressed in papaya ripening and is responsible for pulp softening 17,19 . The PG action modifies the pectin structures and releases them into the WSF of the fruit pulp resulting in a shift from long galacturonan chains to medium chains 17,18 .…”
Section: Discussionmentioning
confidence: 99%